From Pinocchio to Pancasila: A Comparative Study of International Literary Values and Indonesian Culture - Ananto, Gigih Dwi; Iman Jauhari; Pigai, Zeth Kinaukaga (Universitas Kristen Cipta Wacana, 2025)
This study examines the moral values embedded in the Western children’s narrative Pinocchio and evaluates their compatibility with Indonesian cultural ethics. While Western stories have long been introduced into Indonesian classrooms and media, limited research has critically analyzed how their underlying cultural norms interact with local values. Using qualitative content analysis based on Ary et al.’s research framework, this study analyzed five thematic constructs found in Pinocchio—honesty, obedience to parents, responsibility, helping others, and identity formation—against Indonesian moral principles rooted in budi pekerti, communal harmony, filial duty, and social responsibility. Findings indicate that although Pinocchio shares universal virtues relevant to Indonesian culture, tensions arise in how these values are conveyed. Western narratives frame moral development as individualistic self-realization through rebellion and personal consequence, whereas Indonesian ethics view character formation as relational, socially mediated, and spiritually grounded. The study concludes that Pinocchio can reinforce Indonesian character education when culturally interpreted rather than directly adopted. It recommends culturally responsive pedagogy where educators guide students to reinterpret global literature through Indonesian values, enabling foreign narratives to enrich rather than contradict local moral identity. The study contributes to cross-cultural literary analysis, character education discourse, and curriculum development in multicultural contexts.